Penggunaan Zeolit Alam Sebagai Media Penyaring Air Dalam Skala Rumah Tangga Pada Kawasan Karst Malang Selatan - Nelya Eka Susanti; Yuli Ifana Sari; Ninik Indawati (Abdimas Mandalika, 2023)
Abstract:  In the springs in Sumberagung Village, Sumbermanjing Wetan District, there is an HCO3- content of 565.50 mg/l (Perdana, 2016). The dissolved HCO3- content in the karst springs makes the water unfit for daily use. So from this situation, it is necessary to have appropriate technology in an effort to minimize substances dissolved in water by filtering clean water so that it is more suitable for use by the community for household needs. Community service by using natural zeolite as a filter media has the following work procedures: 1) collecting water filter materials, 2) making an installation design framework, 3) compiling natural zeolite into the installation, 4) product trials, 5) making media posters or banners regarding the dangers of lime content for health, and also regarding the stages of making a water filter installation so that the general public can read it. The results obtained from community service activities are as follows: 1) fulfillment of water filter material in the form of natural zeolite, 2) arrangement of the installation design framework for water filter media, 3) arrangement of water filter material into the installation, 4) ready-to-use products, 5) media posters as a medium of socialization has been accepted by society.Abstrak: Pada mataair di Desa Sumberagung Kecamatan Sumbermanjing Wetan terdapat kandungan HCO3- sebesar 565,50 mg/l (Perdana, 2016). Kandungan HCO3- yang terlarut pada mataair karst tersebut membuat kondisi air kurang layak digunakan untuk keperluan sehari-hari. Sehingga dari situasi tersebut perlu adanya teknologi tepat guna sebagai upaya meminimalisir zat yang terlarut dalam air dengan melakukan penyaringan air bersih agar lebih layak digunakan oleh masyarakat untuk keperluan rumah tangga. Pengabdian kepada masyarakat dengan menggunakan zeolit alam sebagai media penyaring memiliki prosedur kerja sebagai berikut: 1) mengumpulkan bahan penyaring air, 2) membuat kerangka desain instalasi, 3) menyusun zeolit alam ke dalam instalasi, 4) uji coba produk, 5) pembuatan media poster atau spanduk mengenai bahaya kandungan kapur bagi kesehatan, dan juga mengenai tahapan pembuatan instalasi penyaring air agar bisa dibaca oleh masyarakat secara umum. Hasil yang diperoleh dari kegiatan pengabdian adalah sebagai berikut: 1) terpenuhinya bahan penyaring air berupa zeolit alam, 2) tersusunnya kerangka desain instalasi media penyaring air, 3) tersusunnya bahan penyaring air ke dalam instalasi, 4) produk siap digunakan, 5) media poster sebagai media sosialisasi telah diterima masyarakat.